Isolation, culture, characterization and cryopreservation of stem cells derived from amniotic mesenchymal layer and umbilical cord tissue of bovine fetuses - Campos, Loreta L. [UNESP]; Landim-Alvarenga, Fernanda C. [UNESP]; Ikeda, Taticia L. [UNESP]; Monteiro, Bianca A. [UNESP]; Maia, Leandro [UNESP]; Freitas-Dell'Aqua, Camila P. [UNESP]; De Vita, Bruna [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2017)
Stem cells are undifferentiated cells with a high proliferation potential. These cells can be characterized by their in vivo ability to self-renew and to differentiate into specialized cell lines. The most used stem cell types, in both human and veterinary fields, are the mesenchymal stem cells (MSC) derived from bone marrow and adipose tissue. Nowadays, there is a great interest in using stem cells derived from fetal tissues, such as amniotic membrane (AM) and umbilical cord tissue (UCT), which can be obtained non-invasively at delivery time. Due to the scarcity of studies in bovine species, the aim of this study was to isolate, characterize, differentiate and cryopreserve MSC derived from the mesenchymal layer of amniotic membrane (AM), for the first time, and umbilical cord tissue (UCT) of dairy cow neonates after assisted delivery (AD) and from fetus at initial third of pregnancy (IT) obtained in slaughterhouse. Cells were isolated by enzymatic digestion of the tissue fragments with 0.1% collagenase solution. Six samples of AM and UCT at delivery time and six samples of AM and UCT at first trimester of pregnancy were subjected to morphology evaluation, imunophenotype characterization, in vitro osteogenic, adipogenic and chondrogenic differentiation and viability analysis after cryopreservation. All samples showed adherence to plastic and fibroblast-like morphology. lmmunocytochemistry revealed expression of CD 44, NANOG and OCT-4 and lack of expression of MHC II in MSC from all samples. Flow cytometry demonstrated that cells from all samples expressed CD 44, did not or low expressed CD 34 (AM: IT -0.3%(a), AD -3.4%(b); UCT: 0.4%, 1.4%) and MHC II (AM: IT -1.05%(a), AD-9.7%(b); UCT: IT-0.7%(a), AD-5.7%(b)). They were also capable of trilineage mesenchymal differentiation and showed 80% viability after cryopreservation. According to the results, bovine AM and UCT-derived cells, either obtained at delivery time or from slaughterhouse, are a painless and non-invasive source of MSC and can be used for stem cell banking.
Keywords: Holstein cow; cell banking; MHC class II; fetal annexes; immunophetotype